Parkinson's disease (PD) is the most common neurodegenerative disease - P. A. Andoskin; A. K. Emelyanov; M. A. Nikolaev; K. A. Senkevich; V. P. Shilin; A. F. Yakimovskiy; A. A. Timofeeva; S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Metabolic impairment of alpha-synuclein protein is considered to be the central event in PDpathogenesis. Recent studies explored usage of alpha-synuclein in peripheral fluids as a biomarker of PD, however alpha-synuclein level in the CSF and plasma is considered to be affected by hemolysis. In order to avoid contamination of a lymphocyte fraction by erythrocytes, we have proposed an algorithm based on measurements of alpha-synuclein levels in the homogeneous CD45+ cell blood fraction. For this study we formed a group of PD patients (N=14) and a control group without the neurological disorders (N=17). We found an increase in the level of the total alpha-synuclein in CD45+ cells of PD patients compared to controls (p = 0,04), and revealed a direct correlation between the level of dopamine in plasma and level of total alpha-synuclein in CD45+ cells in the control group (r=0,71, p = 0,007).The level of alpha-synuclein in CD45+ cells could be suggested as possible PD biomarker.